Putting the 'culture' in agriculture traditional Ifugao rice farmers' receptions of modern agricultural technologies mediated by the Philippine Department of Agriculture - Reyes, Pamela Renee Capulong
The landscape of traditional Ifugao rice farming is changing, partly due to modern technologies provide and communicated by the Department of Agriculture (DA). This study aimed to describe the reception of traditional Ifugao rice farmers towards these modern technologies mediated by the DA. Stuart Hall's Reception Theory--integrated with a Cultural Ecology framework based on the works of anthropologists Julian Steward and Leslie White--was employed for this purely qualitative study. Ethnographic interview was the main research method used. The indigenous cultural backgrounds of farmers were established in detail to provide proper context for their reception. Unlike most reception studies, the study elaborated on all three possible decoding outcomes. It was found among the traditional rice farmers of Banaue and Kiangan, Ifugao that expressions of Negotiated Readings are mostly influenced by their attitudes; Oppositional Readings were tied strongly to their Ideologies; and Dominant Readings were generally related with the Social Structures that exist in their farming communities-particularly the ones relating to economic development. Although this study elaborated on all three reception outcomes, it was observable that Dominant Readings were the most prominent expressions of reception.